2018
DOI: 10.1016/j.vaccine.2018.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Identification of suitable adjuvant for vaccine formulation with the Neospora caninum antigen NcSRS2

Abstract: The parasite Neospora caninum is the main cause of abortion in cattle in many countries around the world, so a vaccine is a rational approach method for the control of the disease. An effective vaccine should be able to prevent both, the horizontal and vertical transmission of N. caninum. In this study, the immune vaccinal response of the recombinant protein rNcSRS2 of N. caninum expressed in Pichia pastoris and formulated with water-in-oil emulsion, xanthan gum, and alum hydroxide was assessed in an experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, in our previous study, we do not observe upregulation of the IL4 in female outbred Swiss albino mice splenocytes stimulated for 18 h with 10 μg of rgD5 [10]. Nevertheless, a similar effect toward a Th1 response using an oil-based adjuvant was reported [48,49], when a TLR ligand agonist was used. Except for TLR-9, significant upregulation of all TLRs has been detected following primary infection of neural tissues by both BoHV-1 and -5 herpesviruses, but the role of gD in this mechanism is not totally known [50].…”
Section: Discussionmentioning
confidence: 51%
“…However, in our previous study, we do not observe upregulation of the IL4 in female outbred Swiss albino mice splenocytes stimulated for 18 h with 10 μg of rgD5 [10]. Nevertheless, a similar effect toward a Th1 response using an oil-based adjuvant was reported [48,49], when a TLR ligand agonist was used. Except for TLR-9, significant upregulation of all TLRs has been detected following primary infection of neural tissues by both BoHV-1 and -5 herpesviruses, but the role of gD in this mechanism is not totally known [50].…”
Section: Discussionmentioning
confidence: 51%
“…Our group, studying the immune response of a recombinant glycoprotein gD (rgD5) of Bovine Herpes virus (BoHV-5) adjuvanted with Montanide ISA50V2, in a mice model, showed similar results, where higher antibodies titers were obtained at day 28 th and maintaining these high levels up to the end of the experiment (Dummer et al, 2014). Pinheiro et al (2018), studying the role of different adjuvants in the immune response to a Neospora caninum recombinant protein (rNCSRS2), reported very similar results, with a significant vaccinal response after the boost, and an IgG1/IgG2 profile similar to this study, corroborating with a Indicate the groups that showed statistically significant differences (P < 0.05) when compared with the control group.…”
Section: Discussionmentioning
confidence: 86%
“…Pregnant mice immunized with T. gondii GRA17 or GRA24 produced high levels of IL-10, which could modulate the pathological damage in foetal mice induced by a large amount of the Th1 cytokine IFN-γ induced by T. gondii challenge [31,39]. BALB/c mouse vaccination with the recombinant protein rNcSRS2 of N. caninum promoted the upregulation of IL-10 expression [40]. Another study also reported a role for B cells in cytokine production in mouse spleen cells, especially IFN-γ and IL-10, in mice restimulated with Neospora antigens.…”
Section: Discussionmentioning
confidence: 99%